Listening to Trypho - Horner, T (2000)
﻿ The primary focus of this thesis is the figure of Trypho in Justin Martyr's Dialogue with Trypho, A Jew (mid-second century C.E.). The substance of the thesis is an analysis of Trypho's depiction and function within the text. Focusing exclusively on Trypho provides a new lens through which to view the Dialogue. This approach has revealed instances where Justin's apologetic breaks down and gives an unintended glimpse behind the text. Lifting Trypho out of the text reveals a consistent figure who does not appear to be based on any Jewish stereotype or Christian invention. He is neither Justin's puppet nor is he blindly obdurate. Instead he is depicted as a pre-rabbinic Diaspora Jew whose argumentation style is philosophical, even Socratic. The depiction reveals a voice with its own sensibility, style, and agenda. It is a voice which defies fiction. This process has also caused a reconsideration of the entire text of the Dialogue and its development. This thesis puts forward the hypothesis that within the text of the Dialogue there is a core-text comprised almost exclusively of dialogue material. I have named this hypothetical text the Trypho Text. This reconstructed Trypho Text forms a more cohesive and understandable document than our extant Dialogue and is less than half the size. This thesis provides evidence to support the idea that the Trypho Text comprised what appears to be the core of the original Dialogue (ca. 135 C.E.) with large amounts of LXX and Christian material inserted at a later date (ca.157 C.E.). In establishing an authentic Jewish figure within this second-century Christian document, this thesis hopes to enhance our understanding of Jewish/Christian relations during this formative period. The investigation of Trypho is an important and significant work for our understanding of early Christianity, Greco-Roman Judaism, and the relationship between them.